ANALISIS PENDAPATAN USAHATANI ANGGOTA KOPERASI DAN NILAI TAMBAH PRODUK OLAHAN KOPI DI KOPERASI AGRO PANCA BHAKTI KABUPATEN LAMPUNG BARAT - Fenti Gasanova; Dyah Aring Hepiana Lestari; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This research aims to analyze income farming of cooperative members and added value of processed products of coffee at cooperative Agro Panca Bhakti. This research was purposively conducted at Cooperative Agro Panca Bhakti, Sekincau, West Lampung Regency from May to July 2018 with 34 respondents cooperative members and 4 respondents cooperative management. The data of this research were collected by using case study method and were analyzed descriptively by income farming analysis and value added method by Hayami. The results of this research showed that the average of income based on total cost per year received by cooperative members was Rp11.012.188,82 per hectare. Processed products of coffee at cooperative Agro Panca Bhakti was viable development because it has positive added value.Keywords : coffee, income farming, value added